Nukiangendines A and B, two novel 13, 14-seco-abietanes from Abies nukiangensis. Issue 10 (7th March 2019) - Li, Yong-Li; Zhang, Qiang; Wu, Jian-Jun; Xue, Li-Jun; Chen, Li-Ming; Tian, Jun-Mian; Xu, Zhuo-Ni; Chen, Ying; Yang, Xian-Wen; Hao, Xiao-Jiang; Li, Jie
Graphical abstract: Highlights: Two novel 13, 14- seco -abietane diterpenes were obtained. Nukiangendine A (1 ) bears a novel structure with a 6/6/6/5 ring system. Nukiangendine A (1 ) exhibited potent anti-HCV effect. Abstract: From Abies nukiangensis, two novel 13, 14- seco -abietane diterpenes, nukiangendines A (1 ) and B (2 ) were isolated. Their relative structures were determined by extensive NMR and HRMS spectroscopic analysis. The absolute configuration of1 was established by ECD calculations. Compound1 showed significant anti-hepatitis C virus (HCV) effects.